STRATEGI UNIT PENGELOLA KEGIATAN (UPK) SYARIAH TUJUAH SARUMPUN DALAM PEMBERDAYAAN EKONOMI MASYARAKAT KECAMATAN AMPEK ANGKEK KABUPATEN AGAM - Anisa Putri; Septria Susanti (BORJUIS: JURNAL OF ECONOMY, 2025)
This research is motivated by the economic decline of the community in Ampek Angkek in recent years. The research aims to analyze the appropriate strategy for empowering the community's economy carried out by UPK Syariah Tujuhah Sarumpun. The method used in this research is a qualitative method and analyzed using SWOT Analysis. After conducting research, several results and findings were obtained. In the implementation of community economic empowerment, the formation of a Sharia UPK Joint Business Group was discovered. Sharia Micro Funding and Inviting people to save. Strategy analysis revealed several WT strategies that could be implemented by UPK Syariah Tujuah Sarumpun in the form of: Updating regulations but remaining firm. Improving the financial management of UPK Syariah Tujuah Sarumpun. Providing education and spiritual encouragement to UPK Syariah employees to raise self- motivation. Recruit better human resources, so they can carry out their duties optimally. Then several inhibiting factors were also found in community economic empowerment, namely: Limited facilities, resulting in less than optimal community empowerment, the existence of people who were less honest and lacked commitment in implementing existing programs. The public lacks understanding of bookkeeping and good financial management. The limited funding provided by UPK Syariah means that the impact felt by the community in economic empowerment is less. Then, supervision is carried out by forming a supervisory team, implementing periodic reporting, field visits, program evaluation, conducting financial audits, Sharia supervision.